Upacara Pemakaman Saurmatua Sebagai Pendampingan Berbasis Budaya: Studi Kasus Di Desa Hutaraja Kabupaten Humbang Hasundutan - Purba, Sanny (JURNAL DIAKONIA, 2022)
The saurmatua funeral ceremony is a funeral ceremony carried out for someone who died in a status where all of his descendants are married and already have children. The saurmatua funeral ceremony can be used as cultural-based guidance through the values ​​contained in its implementation stages and the elements contained in it, namely mangalean ulos (give an ulos), manortor (dancing), margondang (play the music), to mandok hata (saying a consolation word).